Reabilitação psicossocial e sofrimento psíquico do indivíduo: imagens e significados compartilhados pela família - Macedo, Adriana Maria Bento (2001)
The insanity concept have sufíered many modifications for a long time, wich changed the kind of assistance offered to the patients and the health team. We search the Social Representation of the insanity concepcion of their relatives mfluenced in the Psycossocial Reabilitation process in person, investinging how anchor the images and prototypes about the madness. The procedure for the collect data has been a personal depositation of the fifteen (15) mental sick relatives atended for a Psycosocial Atention Center (CAPS) and a Mental Health ambulatory (NAMI), The study is a qualitative one. The data collect was mode between october and november 2000. The results analysis was mode the Contents Analisys principie (BARDIN) ans Social Representation (MOSCOVICI). We concluded that the Social Representation of the insanity concept show the centers meaning Myself Out (42,3%), Psychic Uneasiness (36%) and Sick (21,6%). The relatives feel the insanity from association of the psycossocial clauses, psycobiologies ans sociai- culturals. The insanity perception that a psycossocial phenomenon influenced the relatives atuation in the Psycossocial Reabilitation process. How to the seach for the institutions that favoreded this process.